2000
DOI: 10.1172/jci10196
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a potent humoral response associated with immune-induced remission of chronic myelogenous leukemia

Abstract: The effectiveness of donor-lymphocyte infusion (DLI) for treatment of relapsed chronic myelogenous leukemia (CML) after allogeneic bone marrow transplantation is a clear demonstration of the graft-versus-leukemia (GVL) effect. T cells are critical mediators of GVL, but the antigenic targets of this response are unknown. To determine whether patients who respond to DLI also develop B-cell immunity to CML-associated antigens, we analyzed sera from three patients with relapsed CML who achieved a complete molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 58 publications
7
107
0
Order By: Relevance
“…All accession numbers refer to the BLAST database (http://www.ncbi.nlm.nih.gov/BLAST). hCAP-G and APOBEC3B were used for further analysis since these genes are known to have tissue-restricted expression profiles and are SEREX-defined antigens in melanoma patients (Jager et al, 2000b) and a DLI-responder with CML (Wu et al, 2000), respectively. The expression of hCAP-G mRNA is highest in the testis and low in other normal tissues.…”
Section: Hcap-g Sart-1 Apobec3bmentioning
confidence: 99%
“…All accession numbers refer to the BLAST database (http://www.ncbi.nlm.nih.gov/BLAST). hCAP-G and APOBEC3B were used for further analysis since these genes are known to have tissue-restricted expression profiles and are SEREX-defined antigens in melanoma patients (Jager et al, 2000b) and a DLI-responder with CML (Wu et al, 2000), respectively. The expression of hCAP-G mRNA is highest in the testis and low in other normal tissues.…”
Section: Hcap-g Sart-1 Apobec3bmentioning
confidence: 99%
“…These patients thus represent a unique opportunity to examine a consistently effective antitumor response in vivo. Although T cells are presumed to be the critical mediators of graft-versus-leukemia, our previous studies have shown that DLI initiates a complex immune response that includes a potent antibody response to a variety of leukemia-associated antigens (16). Using established methods for serological identification of tumor antigens by recombinant cDNA expression cloning (SEREX) (17,18) we identified a panel of 13 leukemia-associated antigens that were recognized by high titer antibody 1 year after response to DLI.…”
mentioning
confidence: 99%
“…Studies of CML and myeloma patients demonstrate that GVL or GVM responses are correlated with the development of potent antibody response to antigens which are highly expressed on tumor cells. 32,33 These potential target antigens in CML (CML66 and CML28), and in myeloma (BCMA) have been characterized. [33][34][35][36] Therefore, CD4 þ DLI appears to have a broad effect on immunity, providing help for the expansion of cytolytic CD8 þ donor T cells and also facilitating the development of potent antibody response to potential target antigens.…”
Section: Discussionmentioning
confidence: 99%